2007
DOI: 10.1002/pbc.21448
|View full text |Cite
|
Sign up to set email alerts
|

Impact of childhood cancer on parental employment and sources of income: A Canadian pilot study

Abstract: It appears that the diagnosis of childhood cancer may cause an important but short-term impact on the employment and income sources of affected families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 23 publications
8
87
0
1
Order By: Relevance
“…These results are in line with previous studies showing that a majority of parents are able to return to stable income and employment within five years after diagnosis [3,5]. We have previously reported on the consequences of having a child with cancer on work situation, sick leave and income in this cohort and shown that although mothers reported more sick leave, their work situation at one year after end-of-treatment appeared normalized, whereas fewer fathers were working compared with pre-diagnosis [9].…”
Section: Interpretation Of Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…These results are in line with previous studies showing that a majority of parents are able to return to stable income and employment within five years after diagnosis [3,5]. We have previously reported on the consequences of having a child with cancer on work situation, sick leave and income in this cohort and shown that although mothers reported more sick leave, their work situation at one year after end-of-treatment appeared normalized, whereas fewer fathers were working compared with pre-diagnosis [9].…”
Section: Interpretation Of Resultssupporting
confidence: 83%
“…There is a lack of longitudinal studies with long-term follow-up on the impact of childhood cancer on parents' work situation. However, some studies have found a majority of families reporting employment and income levels comparable with pre-diagnosis levels within five years following diagnosis [3,5]. One large population-based Norwegian study, where the majority of children were diagnosed more than five years earlier, found limited adverse effects of childhood cancer on parents' employment [5].…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…6 This includes 11% to 35% of parents who quit their jobs to care for their children, 5,6,10 although this effect may be short-lived. 10 A major limitation of this growing body of literature is that the economic consequences of the end-of-life period have been neglected. Only two studies included a small number of bereaved parents, 8,10 and neither described their experiences in…”
Section: Introductionmentioning
confidence: 99%
“…27 The fact that CAT measures were not captured demonstrates that there may be newer, but well-validated, measures that have not yet generated enough research to have been captured in a review. 27,67 The PHQ-9 is another good example, because while it was reviewed less favourably in this meta-review, recent research suggests it may be a promising screener 12 and case-finder, 68 and may be quite responsive. 69 The captured reviews also provided different data and used different methods, making it difficult to draw firm conclusions, however future meta-reviews could utilize more sophisticated tools (such as Rasch measurement) to allow a common metric to be generated for different depression measures.…”
Section: Meta-review Limitationsmentioning
confidence: 99%